2017
DOI: 10.1177/0269215517695372
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of prolonged disorders of consciousness on caregivers: a systematic review of quantitative studies

Abstract: Review methods: Studies were included that used quantitative methodologies and psychological measures to investigate experiences. The PRISMA statement was followed with inclusion criteria set a priori. A data synthesis summarised psychological constructs studied.Results: A total of 18 studies (ranging between n=16 -487 participants) met the inclusion criteria with 15 of 18 studies focused on the primary caregiver. A total of 23 standardized psychological measures were identified to assess four primary psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(169 reference statements)
4
16
0
Order By: Relevance
“…The literature has shown that families of PDOC patients experience significant distress following profound brain injury (Kitzinger and Kitzinger, 2014). A systematic review by Soeterik et al (2017) found that some caregivers exhibit clinically significant levels of grief, burden, wellbeing changes and coping difficulties, which may remain the same or deteriorate over time. The findings from the present study suggest that this has implications for clinicians providing care for these patients, who may not only be affected personally by the cases they come across, but find themselves in difficult roles as key workers where they feel a responsibility to alleviate family distress.…”
Section: Dealing With Family Expectationsmentioning
confidence: 99%
“…The literature has shown that families of PDOC patients experience significant distress following profound brain injury (Kitzinger and Kitzinger, 2014). A systematic review by Soeterik et al (2017) found that some caregivers exhibit clinically significant levels of grief, burden, wellbeing changes and coping difficulties, which may remain the same or deteriorate over time. The findings from the present study suggest that this has implications for clinicians providing care for these patients, who may not only be affected personally by the cases they come across, but find themselves in difficult roles as key workers where they feel a responsibility to alleviate family distress.…”
Section: Dealing With Family Expectationsmentioning
confidence: 99%
“…, Soeterik et al . ). Despite being a small group, PDOC patients also place a large financial burden on the NHS.…”
Section: Introductionmentioning
confidence: 97%
“…They are first resource of care, especially for patients with long-term and permanent needs (14). The caregivers experience a variety of distresses, prolonged grief, depressive symptoms, physical and financial burden, and social problems (15). This situation is much worser in Iran, due to some resource limitations in health care settings (16), and staff shortage (16), hence, the caregivers of PVS need support and help (17).The studies mostly focused on the care-giving challenges of PVS at home (18;19), and there is a lack of studies on this issue in hospitals.…”
Section: Introductionmentioning
confidence: 99%